Representaciones sociales acerca de la delincuencia que tienen las menores de edad institucionalizadas en un centro de reeducación de la ciudad de Bogotá (2010)
The general objective that this investigation had was to know the social representations that the underage boarders have in a closed institution of reeducation in Bogotá city, especially in the location stage. By the way, the methodology used was the discussion technique of the focal group and from the speech analysis it was set out the following categories of analysis: delinquency conceptualization, attribution of responsibility, legitimacy of criminal acts and future. The results that were analyzed according with those categories show that the social representations about delinquency are the result of its conceptualization from the consequences, assessment, origin, instrumentation and knowledge. The attribution of responsibility in delinquency focuses in itself in relationship with others in family, social life and the opportunities that society offers. The future prospect gets influenced in the levels: personal, institutional and social.